An Analysis of Students’ Ability in Speaking Through Describing and Drawing Technique at Eighth Grade of SMP Swasta Bunga Mawar - Reita Solagracia Telaumbanua; Riswan Zega; Yaredi Waruwu; Kristof Martin Efori Telaumbanua (ITScience (Information Technology and Science), 2024)
Speaking is expressing ideas, feelings, and desires that need to be represented to others in the form of speech. The research aimed to describe the student's ability to speak and to find out the reasons for students' ability to describe a person through describing and drawing techniques in the eighth grade of SMP Swasta Bunga Mawar. The method used in the research was the qualitative method. The participants were 16 students in the eighth grade of SMP Swasta Bunga Mawar. The instruments used to get the data were tests, interviews, and observations. After obtaining the data, the researcher analyzed them using quantitative and qualitative techniques. The results showed that in the students' ability to speak through describing and drawing techniques, two students (12.5%) achieved outstanding category, seven students (44%) achieved good category, six students (37.5%) achieved enough category, and one student (6%) achieved less category. Then, the reasons students' ability to describe people through describing and drawing technique because this technique has eleven advantages: enhances students' vocabulary, makes learning more attractive, makes students interact with their friends, motivates them to speak, encourages them to be active in learning, enthusiastic, enhance their self-confidence, comfortable, the learning process not stuffy, convenient to describe something, and excite them to speak fluently. So, it can be concluded that the student's ability to talk through describing and drawing techniques in the eighth grade of SMP Swasta Bunga Mawar was good. The researcher suggests that teachers use this technique when teaching speaking.